2011
DOI: 10.1002/ejoc.201100489
|View full text |Cite
|
Sign up to set email alerts
|

A New Solvent‐Free Reaction for the Preparation of Alkoxysilane from Cyclic Ethers, Alcohols, or Carbonyl Compounds

Abstract: The 1,1,3,3‐tetramethyldisiloxane/Pd/C system is reported here as a new method to accomplish the ring‐opening of ethers and epoxides to give protected alcohols. The approach can also be used for the protection of primary or secondary alcohols and for the reduction of aldehydes and ketones to obtain alkoxysilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…131), hexane oxide gave a mixture of isomeric silylated alcohols. 114 Tetrahydrofurans also gave alkoxysilanes via a reductive ring opening (Eq. 132).…”
Section: Miscellaneous Tmds Reductionsmentioning
confidence: 99%
“…131), hexane oxide gave a mixture of isomeric silylated alcohols. 114 Tetrahydrofurans also gave alkoxysilanes via a reductive ring opening (Eq. 132).…”
Section: Miscellaneous Tmds Reductionsmentioning
confidence: 99%
“…More recently, we and others reported mild, safe, and efficient reduction procedures by using TMDS12 for the direct conversion of a range of functions such as phosphane oxides,11 nitriles,13 amides,14 nitro,15 esters,16 and ketones17 depending on the nature of the metal catalyst. We have shown that, by using a stoichiometric amount of Ti(O i Pr) 4 , aromatic or aliphatic nitriles could be readily converted into the corresponding primary amines in high yield 13.…”
Section: Resultsmentioning
confidence: 99%
“…Lemaire and co‐workers applied a catalytic system of Pd/C ( 11 )/TMDS for the high‐yielding hydrosilylation of epoxides (Scheme ) . The hydrosilylation of epoxides with TMDS (0.5 equiv) in the presence of 11 (1.2 mol %) proceeded under neat conditions to give the corresponding silyl‐protected alcohols.…”
Section: Hydrosilylative Reduction Of Epoxidesmentioning
confidence: 99%
“…[35] Lemaire and co-workers applied ac atalytic system of Pd/C (11)/TMDS for the high-yielding hydrosilylation of epoxides (Scheme 21). [36] The hydrosilylationo fe poxides with TMDS (0.5 equiv) in the presence of 11 (1.2mol %) proceeded under neat conditions to give the corresponding silyl-protected alcohols. Although the reaction of styrene oxide wasq uantitative and selective, to give the alkoxydisiloxane in excellent yield, 1,2-epoxyhexane was converted into as tatistical mixture of three hydrosilylative products in ac ombined yield of 99 %.…”
Section: Hydrosilylative Reduction Of Epoxidesmentioning
confidence: 99%